THE INFLUENCE OF MARKETING MIX ON THE DECISION TO PURCHASE COFFEE DRINK AT AMMA SPOT COFFEE SIMPANG PERUMNAS LANGSA - Anandita, Lyra (AGRIBUSINESS JOURNAL, 2024)
This research aims to evaluate the influence of the marketing mix on the decision to purchase coffee drinks at Amma Spot Coffee Simpang Perumnas, Langsa City. The sampling method used was nonprobability sampling in the form of accidental sampling with a sample size of 96 people. To see the influence of the marketing mix (X1) product, (X2) price, (X3) place, and (X4) promotion on the variable (Y) decision to purchase coffee drinks at Amma Spot Coffee Simpang Perumnas, Langsa City, the author uses the multiple linear regression method. Data analysis was carried out using SPSS 20 computer software. The research results showed that price (X3) and place (X4) had a very real influence and promotion (X4) had a real influence on the decision to purchase coffee drinks at Amma Spot Coffee Simpang Perumnas, Langsa City. Meanwhile, the product variable has no influence on the decision to purchase coffee drinks at Amma Spot Coffee Simpang Perumnas, Langsa City.